The Difficulties of Speech Skills Instruction in Intensive Arabic Language Program (Descriptive Study of Arabic Language Instruction at Islamic State Institution, Kadiri) - Nida’, Khoirun (Faculty of Education and Teachers Training of UIN Sayyid Ali Rahmatullah Tulungagung, 2017)
Intensive Program of Arabic language instruction were four classes, namely the first for students who have excellent competence, the second for students who have good compentence, the third for students in intermediate competence, and the forth for students in basic competence. The objectives of dividing classess were to facilitate the instruction process and to know the appropriate instruction method that was used and to evaluate. The process of Arabic instruction is twenty five percent using Arabic language and the most. The methods, that was used, are direct method, audio and verbalizing. Those equipments were expected students to have four skills of language. The book, that was used in Arabic language instruction mostly, is “Baina Yadaik” . The process of Arabic learning instruction by using various method and good book resources still found problem, especially in speech skill (maharoh kalam).